ChatGPT as a translator’s aid: the perspective of applied linguistics students - Zagórska, Anna (Kwartalnik Neofilologiczny, 2026)
In recent years, generative Artificial Intelligence has introduced tools that were unimaginable until recently. Although translators and teachers acknowledge the usefulness of ChatGPT, many language professionals are still unable to use it effectively and express concerns about the quality of its output. The article presents the results of a study conducted at the Institute of Specialised and Intercultural Communication, Faculty of Applied Linguistics, University of Warsaw. The participants were asked to complete a questionnaire devoted to the use of ChatGPT in translators’ work. The questionnaire included open-ended questions on the quality of the output generated by the chat, as well as closed-ended questions allowing for quantitative analysis of the subject under investigation.